Functional Outcome of Subvastus versus Medial Parapatellar Approaches for Total Knee Replacement in Patients with Knee Osteoarthritis: A Prospective Cohort Study - Adnan Ahmed Aladraii; Lama Zaki Allehaibi; Amjad Abdulrahman Fattani; Taif Abdullah Alkhudairy; Albatoul Mohammed Al-Margan; Sami Abdo Radman Al-Dubai; Abdulrahman Abdulraof Mohammed; Doaa K Mohorjy; Abdulhakeem Saeed Alqarni (Saudi Journal of Medicine and Medical Sciences, 2024)
Background: Subvastus approach and medial parapatellar approach are two major approaches for total knee replacement (TKR). There is no global consensus on the superiority of either approach in terms of functional outcomes.